2015
DOI: 10.4067/s0717-95022015000400032
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biometrical Characteristics on Otolith of Barbus tauricus Kessler, 1877 on Light and Scanning Electron Microscope

Abstract: SUMMARY:The otolith morphology, biometry and the relationship between the otolith size and fish length were examined. The weight, length, width, area and perimeter were recorded for each pair of otoliths. The values of form factor (FF), roundness (RD), aspect ratio (AR), circularity (C), rectangularity (R) and elipticity (E) were calculated and the relationships between otolith length (OL) and shape indices were showed with graphics. According to paired t-test results, difference between right and left otolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
(13 reference statements)
5
8
0
1
Order By: Relevance
“…These findings are in agreement with the observations of many authors who reported that, the sex difference had statistically non-significant effect on the otolith length [15,25,42]. There was no difference between females and males for mean length and weight values (t test, P>0.05) [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in agreement with the observations of many authors who reported that, the sex difference had statistically non-significant effect on the otolith length [15,25,42]. There was no difference between females and males for mean length and weight values (t test, P>0.05) [41].…”
Section: Discussionsupporting
confidence: 93%
“…These findings were supported by other studies that considered the otolith pair were mirror images of each other [15,[22][23][24][38][39][40]. The difference between the length of the right and left otolith was statistically insignificant (P>0.05) [41].…”
Section: Discussionsupporting
confidence: 82%
“…Rastrelliger kanagurta, collected from the Oman Sea, exhibited the strong relationship between total length of fish and otolith dimension (Jawad et al, 2011). Kontaş and Bostancı (2015) stated that the changes in the relationship between the otolith and fish size could correspond to the growth somatically between genders. In some fish species, the male could be larger than the female because it is responsible for constructing and defending the nest like Gobiusculus lavescens (Houde, 2001).…”
Section: Otolith Morphologymentioning
confidence: 99%
“…Türkiye'de hem deniz hem de tatlı su habitatlarında yaşayan farklı balık türlerinin otolitleri, balık boyu-otolit ölçümleri ilişkileri Alburnus spp. (Tsagarakis vd., 2015), Barbus grypus (Düşükcan vd., 2015), Barbus tauricus (Kontaş & Bostancı, 2015), Atherina boyeri (Bostancı vd., 2017), Garra rufa (Yedier vd., 2016), Diplodus puntazzo (Bostancı vd., 2016), B. grypus (Düşükcan & Çalta, 2018), Capoeta trutta (Düşükcan, 2018), Pomatomus saltatrix (Bal vd., 2018a), Sarpa salpa (Bal vd., 2018b), Lophius budegassa türünde birikim problemleri , Alburnus cinsinde tür ayrımları (Bostancı vd., 2015), Atherina boyeri türünde stok ve popülasyon ayrımları (Bostancı & Yedier, 2018;Yedier vd., 2019) üzerine yapılan çalışmalarda kullanılmıştır. Ayrıca otolit morfolojisi üzerine Portekiz kıyılarında (Assis, 2003) ve Atlantik Denizi'nde (Tuset vd., 2008) yapılan çeşitli çalışmalar da bulunmaktadır.…”
Section: Introductionunclassified